THE FORGOTTEN GEOGRAPHIC AND PHYSICAL – OCEANOGRAPHIC KNOWLEDGE OF THE PREHISTORIC GREEKS - Mariolakos, I.D (Bulletin of the Geological Society of Greece, 2010)
Many believe that the Greek Mythology is a figment of the vivid imagination of the ancient Greeks. Consequently, the Greek Myths are all fantastic stories. In my opinion, this view is erroneous, at least on the subject concerning the geographic and physical-oceanographic characteristics of the Atlantic Ocean, as these were described mainly by Homer, Hesiod, the Orphics and Plutarch. In the present paper (i) some of the references made by the above mentioned authors are selectively reported, and (ii) the physical and geological validation is given, based on the present-day scientific views and knowledge. Namely, the prehistoric Greeks knew about the Hyperboreans, the island of Ierne (Ireland), the British isle etc., by the Orphics. From the writings of Plutarch, they knew (i) the relative position of the present-day Iceland (Ogygia) and its distance from Britain, (ii) that to the west of Iceland, three other islands are located, where the sun sets for only an hour a day, (iii) that further to the west there is a “great continent”, which surrounds the Ocean and more. Homer and Hesiod wrote that (i) the Ocean is a “river” that flows continuously, (ii) that this river encircles the Earth and (iii) that its flow is turbulent not only on the surface, but in depth as well. Unfortunately, all this knowledge was gradually forgotten by all. This is the reason why Odyssey is considered just an entertaining poem and Ulysses’ nostos a fantastic story, with no trace of historic reality.